Adult siblings of breast cancer patients: a qualitative analysis - Schleper, Laurie Ann, author; Hamilton, Scott B., advisor; Boyer, William N., committee member; Rickard, Kathryn M., committee member; Banning, James H., committee member (Colorado State University. Libraries, 2003)
This qualitative study explored the stories of thirteen adult sisters of breast cancer patients. Participants engaged in interviews during which the following topics were explored: a) support and assistance provided to siblings during their cancer experience; b) the emotional and psychological toll of witnessing a sister's breast cancer diagnosis and treatment; and, c) impact of a sibling's breast cancer diagnosis on the sibling relationship. In addition, participants completed the Lifespan Sibling Relationship Scale (LSRS) regarding their childhood sibling relationship, pre-cancer adult sibling relationship, and post-cancer adult sibling relationship. Analysis of interview data and questionnaire reports indicated that participants provided a great deal of support and assistance to their siblings, experienced heightened fears regarding their own wellbeing as well as their siblings', and experienced an increased closeness in their sibling relationships as a result of the cancer experience. Findings from the present study address a void in the literature by specifically addressing the psychosocial needs of sisters of breast cancer patients. Recommendations for mental health and medical professionals working in the field of oncology are provided.
Keywords: social psychology; oncology